2011
DOI: 10.1007/s10755-011-9207-7
|View full text |Cite
|
Sign up to set email alerts
|

Using Blogs and New Media in Academic Practice: Potential Roles in Research, Teaching, Learning, and Extension

Abstract: Compiling a referenced article for publication in a peer-reviewed journal is traditionally the most respected means of contributing to a body of knowledge. However, we argue that publication of evidence-based information via new media -especially blogging -can also be a valid form of academic scholarship. Blogs allow for rapid sharing of research methods, results, and conclusions in an open, transparent manner. With proper references, blogs and other new media can position academic research in the public spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Blogs build an archive of knowledge and can bridge scholarly university research and the public (LaBelle et al, 2011). While traditional academic publication is a relatively slow process, blogs allow researchers to rapidly share new information, and commenting features allow for a new form of peer discourse within the academic community (Powell et al, 2012). At the same time, content is made available to the general public and often written in clear language with limited jargon.…”
Section: Keys To Successful Engagementmentioning
confidence: 99%
“…Blogs build an archive of knowledge and can bridge scholarly university research and the public (LaBelle et al, 2011). While traditional academic publication is a relatively slow process, blogs allow researchers to rapidly share new information, and commenting features allow for a new form of peer discourse within the academic community (Powell et al, 2012). At the same time, content is made available to the general public and often written in clear language with limited jargon.…”
Section: Keys To Successful Engagementmentioning
confidence: 99%
“…Blogs-personalized web pages where authors write their experiences, ideas, thoughts, and comments-often deal with private and personal issues, but there is a substantial and even increasing number of people using blogs for academic purposes (Powell, Jacob, & Chapman, 2012). S.-H. Yang (2009) even referred to blogs as "learning spaces."…”
Section: Social Media In Educationmentioning
confidence: 99%
“…For instance, one study looking at stem cell conversations related to spinal cord injury and Parkinson's disease on Twitter found that the most shared frequently tweets related to these conditions were those reporting research findings [14]. Other research has suggested that blogs can play a role in rapidly disseminating reliable and transparent information on emerging health research to the public [52]. Both social media and blogs allow for an engaged discussion between experts, advocates and patients and their families.…”
Section: Biasmentioning
confidence: 99%